Angioedema hereditário: perfil clínico dos pacientes em acompanhamento no Ambulatório de Imunodeficiências Primárias do Hospital das Clínicas da Universidade Federal de Minas Gerais - Gustavo Viana Fusaro (2010)
RATIONALE: Hereditary angioedema due to C1 inhibitor deficiency is clinically characterized by relapsing skin and mucosal swelling, abdominal pain and life threatening upper airway obstruction. It still is a disease poor known by doctors and underdiagnosed. METHODS: This study analyzed the characteristics and outcome of patients with hereditaryangioedema from Pediatric Immunology Division of the Clinical Hospital Federal University of Minas Gerais. RESULTS: A total of 31 hereditary angioedema patients have been studied, 18 male and 13 female, with age between one mouth and 40 years. They belonged to eight families and usually had begun to present clinical symptoms within the second decade of life. Diagnosis had been made from 1 month to 40 years after first symptoms. Spontaneous swelling was frequent, but attacks were also precipitated by trauma, pressure and emotional stress. Skin swellings were presented in 15 patients and abdominal pain attacks were related by 12 patients how initial symptoms. Respiratory symptoms were experienced by four patients, two of then presented laryngeal edema. Low levels of C4 had been noticed in all patients. Prophylactic treatment with attenuated androgens was administered in low doses to 28 patients and was totally effective in 24, without significant side effects.CONCLUSION: The described characteristics are similar to those reported in literature and the prophylactic treatment with attenuated androgens has been effective in controlling manifestations. The diagnoses is still late for some patients